2008
DOI: 10.1104/pp.107.115162
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome- and Gibberellin-Mediated Regulation of Abscisic Acid Metabolism during Germination of Photoblastic Lettuce Seeds

Abstract: Germination of lettuce (Lactuca sativa) 'Grand Rapids' seeds is regulated by phytochrome. The action of phytochrome includes alterations in the levels of gibberellin (GA) and abscisic acid (ABA). To determine the molecular mechanism of phytochrome regulation of ABA metabolism, we isolated four lettuce cDNAs encoding 9-cis-epoxycarotenoid dioxygenase (biosynthesis; LsNCED1-LsNCED4) and four cDNAs for ABA 8#-hydroxylase (catabolism; LsABA8ox1-LsABA8ox4). Measurements of ABA and its catabolites showed that a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 51 publications
3
78
2
Order By: Relevance
“…In lettuce, four different NCED genes were identified (Sawada et al, 2008), but their specific expression patterns have not been reported. During seed development, NCED1 was expressed first, followed by NCED2 and then NCED4, while expression of NCED3 was much lower throughout (Figure 4).…”
Section: Nced4 Shows Distinct Expression From Other Nced Genes In Letmentioning
confidence: 99%
See 2 more Smart Citations
“…In lettuce, four different NCED genes were identified (Sawada et al, 2008), but their specific expression patterns have not been reported. During seed development, NCED1 was expressed first, followed by NCED2 and then NCED4, while expression of NCED3 was much lower throughout (Figure 4).…”
Section: Nced4 Shows Distinct Expression From Other Nced Genes In Letmentioning
confidence: 99%
“…In mature lettuce seeds, NCED4 mRNA is present in the embryo, but not in the endosperm ; information on NCED4 expression during lettuce seed development has not been reported. We therefore assayed mRNA dynamics in developing seeds of the four NCED genes identified in lettuce (NCED1-4) (Sawada et al, 2008). NCED2 expression increased first during seed development and then declined ( Figure 4B), followed by a transient increase in NCED1 expression to two-to threefold higher levels ( Figure 4A).…”
Section: Expression Of Nced Family Members and Other Genes During Letmentioning
confidence: 99%
See 1 more Smart Citation
“…, Yamaguchi 2008, Seo et al 2009). Perhaps the seeds of P. aduncum are not responsive to the application of GA 3 but to other gibberellins, such as GA 1 as in lettuce seeds (Sawada et al 2008) or GA 4 and GA 7 as in seeds of Taxus mairei (Chien et al 1998). The application of GA 3 negatively influenced the root protrusion of P. aduncum (figure 20).…”
Section: Resultsmentioning
confidence: 99%
“…Light quality is a key environmental factor that regulates dormancy and germination of numerous species of plants, including cereals and other Poaceae [34,35]. White light, similarly to blue light, represses the germination of barley, Lolium rigidum, and Brachypodium distachyon, whereas red light stimulates the germination of Brachypodium distachyon but does not affect the dormancy of barley [15,28,[36][37][38].…”
Section: Effect Of Light On Aba Metabolismmentioning
confidence: 99%